INKLUSI SOSIAL DALAM EKONOMI BIRU: PELATIHAN DAN PENDAMPINGAN PEREMPUAN PESISIR DALAM PENGOLAHAN HASIL LAUT DI KECAMATAN BANGGAE TIMUR KABUPATEN MAJENE: SOCIAL INCLUSION IN THE BLUE ECONOMY: TRAINING AND MENTORING FOR COASTAL WOMEN IN MARINE PRODUCT PROCESSING IN EAST BANGGAE DISTRICT, MAJENE REGENCY - Yulia Madjid, Irma; Fitriah, Reski; Fitriah, Devita; Adam, Andi Muhammad (Universitas Hang Tuah Surabaya, 2025)
This community service program aimed to promote social inclusion within the blue economy framework by empowering coastal women in Banggae Timur, Majene Regency, West Sulawesi. Traditionally, local marine products were limited to simple processing methods such as frying or grilling, yielding low added value. Through participatory training and mentoring with the Siamasei women’s group, participants were introduced to marine product diversification, particularly the development of flying fish (Hirundichthys oxycephalus) chili paste, a local specialty. The program employed counseling, demonstrations, and hands-on practice. Findings indicate significant improvements in participants’ skills, knowledge, and entrepreneurial motivation. This initiative highlights the potential of women’s empowerment in enhancing household income, diversifying marine-based products, and strengthening their role in sustainable local economic development